2013
DOI: 10.1007/s11606-013-2603-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Race, and Consideration of Bariatric Surgery Among Primary Care Patients with Moderate to Severe Obesity

Abstract: BACKGROUND: Bariatric surgery is one of few obesity treatments to produce substantial weight loss but only a small proportion of medically-eligible patients, especially men and racial minorities, undergo bariatric surgery. OBJECTIVE: To describe primary care patients' consideration of bariatric surgery, potential variation by sex and race, and factors that underlie any variation. DESIGN, SETTING, AND PATIENTS: Telephone interview of 337 patients with a body mass index or BMI > 35 kg/m 2 seen at four diverse pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 31 publications
4
60
0
Order By: Relevance
“…Though not previously assessed in an OSA population, this finding is consistent with overall bariatric utilization data, where women comprise 76–83% of bariatric patients. (1315) Nevertheless, because of the high prevalence of men with OSA, our study is unique among bariatric surgery studies in that men comprised nearly half of the interested population.…”
Section: Discussionmentioning
confidence: 99%
“…Though not previously assessed in an OSA population, this finding is consistent with overall bariatric utilization data, where women comprise 76–83% of bariatric patients. (1315) Nevertheless, because of the high prevalence of men with OSA, our study is unique among bariatric surgery studies in that men comprised nearly half of the interested population.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that men are less likely than women, and African Americans are less likely than Whites, to have considered bariatric surgery [81], while data on other racial and ethnic groups is lacking. Men and African Americans may be less likely to consider bariatric surgery because men and African Americans generally report higher quality of life scores relative to their BMI [82].…”
Section: Introductionmentioning
confidence: 99%
“…This in turn might have an impact on the perception of the general public and patients themselves. Out of the group of patients eligible for surgery, half of the patients would consider WLS as a treatment option if it had been recommended by their physician, but only 20 % stated that they have actually been recommended for WLS by their physician [15]. In addition, when asking physicians whether they would advise a patient who meets criteria for WLS to see a surgeon, only 23.8 % would recommend this [16].…”
Section: Introductionmentioning
confidence: 99%